Design and Development of a Web-Based Inventory Application at the Central Bureau of Statistics of Riau Province - Fikri, Muhammad Haikal; Susilo, Edi (CV. Rayyan Dwi Bharata, 2025)
This study aims to design and develop a web-based inventory application at the Central Bureau of Statistics (BPS) of Riau Province to overcome the limitations of the existing system. The current inventory system is limited in accessibility, lacks real-time updates, fails to record asset mutation history, and does not provide a dashboard visualization of asset conditions. The research uses a Research and Development (RD) method with a prototype approach. The system is developed using Laravel 11 for backend services and ReactJS 18.2.0 for the frontend interface. Functional testing achieved a 100% success rate, demonstrating that all system features perform as expected. Additionally, the application scored high in compatibility and portability across platforms, with good ratings for reliability, security, and maintainability based on SonarQube assessments. The developed inventory application enhances transparency, accountability, and efficiency in managing organizational assets at BPS Riau Province.